Pengaruh Ekstrak Etanol Daun Kenikir (Cosmos caudatus) terhadap Kadar Glutathion Dan Interleukin 6 Serum Tikus Wistar Jantan yang Diberi Pakan Tinggi Kolesterol - I Gusti Agung Dewi Sarihati; I Gusti Ayu Sri Dhyanaputri (Politeknik Kesehatan Tanjung Karang, 2020)
Chronic dyslipidemia, especially in hypercholesterolemia, can directly disrupt endothelial cell function through increased formation of oxidized LDL which will stimulate an inflammatory response including interleukin 6 (IL-6) release. For this reason, it is necessary to have anti-inflammation that can reduce the effects of hypercholesterolemia on blood vessels. Polyphenols have anti-inflammatory effects and kenikir leaves are vegetables that are rich in polyphenols. This study aims to prove the effect of kenikir leaf (Cosmos caudatus) ethanol extract on IL-6 levels of serum of male Wistar rats fed high cholesterol. The method used is a true experimental study with a Post-test Only Control Group Design. Samples using 24 male rats were divided into 4 groups DS, DTK, Ss, and Cc. DTK, Ss and Cc groups were given high cholesterol feed for 20 weeks. In the 17th to 20th weeks the Ss group was given additional simvastatin and the Cc group was given an additional extract of Cosmos caudatus leaf. Whereas the DS group was only given standard feed for 20 weeks. After 20 weeks all rats in all four groups were examined serum GSH and IL-6 levels. The results showed the highest GSH serum levels average in Cc with p-value=0,016 but not different from Ss. IL-6 serum levels in DTK were higher than those of the other three groups and were significantly different with p-value=0,035. The difference occurs between DTK and DS, Ss and Cc, not different between DS, Ss and Cc. The ethanol extract of kenikir leaf influences the serum IL-6 levels of male Wistar rats fed high cholesterol.